(untitled) (Academicia Globe: Inderscience Research, 2023)
Translation plays an important role in the transmission of information that is in official speech. It should be noted that lexical, stylistic, structural and logical features in the texts that are heard at official events require special attention. Despite the fact that a prepared monologue statement in front of a known audience of listeners, which is carefully prepared by a specialist in advance, nevertheless, the level of writing and the purposefulness of writing should often be taken into account when translating. In this article, along with the structural characteristics, the difficulties of simultaneous translation from Korean into Russian are considered.